The Comparison Analysis of the Main Chemical Composition Parameters of Wild Boar Meat and Pork - Erika Bodnárné Skobrák; Károly Bodnár; Edit Mikóné Jónás; János Gundel; András Jávor (Scientific Papers Animal Science and Biotechnologies, 2023)
The chemical composition of wild boar meat from wild boar parks with various habitats and different feeding facilities was analysed. Samples were collected from m. serratus anterior – during the winter hunting period. The protein, the total fat, the saturated and unsaturated fatty acid content were measured and also and those elements which have great importance on human alimentation. The results were compared with other author’s data of the same parameters of pork. The aim of the study was to compare the effect of different feeding systems on the ingredients of wild boar meat, and the accidental analogy with the ingredients of pork. There was no difference in protein content. The value of miristic acid (C14:0) in the samples of extensively and intensively fed group was more favourable than that of pork. Pork contains more MUFA (palmitoleic acid – C16:1). The semi-intensively fed wild boar’s meat and pork contained linoleic acid (C18:3 n3) almost on the same level. The greatest difference was detected in the level of arachidonic acid (C20:4 n6). The samples from all wild boar groups contained more of this fatty acid than it was published about domestic pigs. Out of the microelements, the iodine and zinc had higher value in wild boar meat than in pork.